ANALISIS YURIDIS PENGIKATAN JAMINAN HAK TANGGUNGAN DALAM TAKE OVER CREDIT BANK KONVENSIONAL KE BANK SYARIAH (STUDI PADA PT. BANK MANDIRI SYARIAH KANTOR CABANG PEMBANTU MEDAN SETIA BUDI) - ANDI TRI UTAMI HASJIM (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1.  Prof. Dr. Syafruddin kalo, SH, MHum2.  H. Zamakhsyari Bin Hasballah Thaibm LC, MA, PhD3.  Notaris Dr. Suprayitno, SH, MKn A loan transfer or subrogation is the replacement of creditor’s rights by a third party by paying the debtor’s remaining debt to the initial creditor. The loan transfer from a conventional bank to sharia bank applies the principle of Qardh, sharia bank firstly pays off the debtor’s remaining debt before making the deed. The deed transfers the debts and collateral between the debtor and conventional bank. This is an analytical descriptive research with normative juridical approach. Qualitative analysis method is employed to process and analyze the data resulted from the research. The conclusion is drawn by applying deductive reasoning method through normative framework. The research results demonstrate that there are two factors influencing the loan transfer from a conventional bank to a sharia bank, namely internal and external factors. Internal factors consist of profit from pricing, needs for plafond addition, products with more interesting installment, easy requirements, profit share basis (nisbah), and banking promo.Keywords: Loan Transfer, Collateral, Mortgage, Conventional Bank, Sharia Bank